Combined Analysis of all Three Phases of Solar Neutrino Data from the Sudbury Neutrino Observatory - Collaboration, SNO; Aharmim, B; Ahmed, SN; Anthony, A; Barros, N; Beier, E; Bellerive, A; Beltran, B; Bergevin, M; Biller, S; Boudjemline, K; Boulay, MG; et al. (2011)
We report results from a combined analysis of solar neutrino data from all phases of the Sudbury Neutrino Observatory. By exploiting particle identification information obtained from the proportional counters installed during the third phase, this analysis improved background rejection in that phase of the experiment. The combined analysis resulted in a total flux of active neutrino flavors from 8B decays in the Sun of (5.25 ± 0.16(stat.)+0.11-0.13(syst.))×10^6 cm^{-2}s^{-1}. A two-flavor neutrino oscillation analysis yielded \Deltam^2_{21} = (5.6^{+1.9}_{-1.4})×10^{-5} eV^2 and tan^2θ_{12}= 0.427^{+0.033}_{-0.029}. A three-flavor neutrino oscillation analysis combining this result with results of all other solar neutrino experiments and the KamLAND experiment yielded \Deltam^2_{21} = (7.41^{+0.21}_{-0.19})×10^{-5} eV^2, tan^2θ_{12} = 0.446^{+0.030}_{-0.029}, and sin^2θ_{13} = (2.5^{+1.8}_{-1.5})×10^{-2}. This implied an upper bound of sin^2θ_{13} < 0.053 at the 95% confidence level (C.L.).